2023
DOI: 10.3390/molecules28052216
|View full text |Cite
|
Sign up to set email alerts
|

Geographic Differentiation of Essential Oil from Rhizome of Cultivated Atractylodes lancea by Using GC-MS and Chemical Pattern Recognition Analysis

Abstract: The rhizome of Atractylodes lancea (RAL) is a well-known Chinese herbal medicine (CHM) that has been applied in clinical settings for thousands of years. In the past two decades, cultivated RAL has gradually replaced wild RAL and become mainstream in clinical practice. The quality of CHM is significantly influenced by its geographical origin. To date, limited studies have compared the composition of cultivated RAL from different geographical origins. As essential oil is the primary active component of RAL, a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Zhang et al [44] identified atramacronoids A-C (18)(19)(20) from the rhizomes of A. macrocephala using spectroscopic data analysis, chemical calculations, and X-ray diffraction, which were found to contain an unusual 6/6/5/5/6 skeleton furnished by an unexpected C-8-C-16 linkage. Subsequently, twenty undescribed eudesmane-type sesquiterpenes named atramacronoids D-W (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) were identified in the rhizomes of A. macrocephala using extensive spectroscopic data analysis, Snatzke's rule, ECD calculations, and X-ray crystallographic analysis [45,46]. A chemical investigation of the ethanol extract of A. lancea resulted in the isolation of nine eudesmanetype sesquiterpenoids (41)(42)(43)(44)(45)(46)(47)(48)(49), and their structures were elucidated using spectroscopic techniques and HRESIMS [47].…”
Section: Eudesmane-type Sesquiterpenesmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al [44] identified atramacronoids A-C (18)(19)(20) from the rhizomes of A. macrocephala using spectroscopic data analysis, chemical calculations, and X-ray diffraction, which were found to contain an unusual 6/6/5/5/6 skeleton furnished by an unexpected C-8-C-16 linkage. Subsequently, twenty undescribed eudesmane-type sesquiterpenes named atramacronoids D-W (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) were identified in the rhizomes of A. macrocephala using extensive spectroscopic data analysis, Snatzke's rule, ECD calculations, and X-ray crystallographic analysis [45,46]. A chemical investigation of the ethanol extract of A. lancea resulted in the isolation of nine eudesmanetype sesquiterpenoids (41)(42)(43)(44)(45)(46)(47)(48)(49), and their structures were elucidated using spectroscopic techniques and HRESIMS [47].…”
Section: Eudesmane-type Sesquiterpenesmentioning
confidence: 99%
“…β -eudesmol, atractylon, and hinesol are usually used as chemical markers for evaluating the quality of Atractylodes DC. in different regions [ 22 , 23 , 24 , 25 ]. Many studies have been conducted on Atractylodes DC.…”
Section: Introductionmentioning
confidence: 99%